(untitled) (Research, Society and Development, 2022)
The grieving process is a misunderstood phenomenon and is even more complicated when layered with complexities found at the intersections of urban life in a networked public. In this context, the objective of the present study was to search the literature in an integrative way for authors who emphasized grief and social networks. This is an integrative literature review study with a qualitative approach, where during the search, a total of 361 abstracts were found, distributed differently in relation to the databases, where 11 articles were chosen for reading and study in full, as results of the present review in which it was verified that the methods used by the articles studied, in order to differentiate the most varied forms of evidence to be discussed. As such, this study of grief and the use of social media continues to increase our knowledge base on grief that affects the experience of many people.